A Rare Tropical Stonefly Brahmana flavomarginata (Plecoptera: Perlidae: Acroneuriinae) from Vietnam - Thi Kim Thu Cao; Yeon Jae Bae (Animal Systematics, Evolution and Diversity, 2013)
The perlid stonefly Brahmana flavomarginata Wu, originally described from China from the male adult, is described using reared male and female adults and nymphs from Vietnam. The male adult of B. flavomarginata is distinguished from its congeners by the blackish-brown body color and distinct head marking, hemitergal triangular chitin plates, and a median semicircular smooth subgenital plate (hammer) on the abdominal sternum IX. The female adult has a large and round subgenital plate which extends to the posterior margin of the abdominal sternum X. The nymph can be distinguished by the relatively small compound eyes and the body covered by many long stout setae and short golden brown hair-like setae. This species is known in southwestern China (Yunnan Province) and northern Vietnam (Lao Cai Province, Cao Bang Province).